El cacao en la Costa ecuatoriana: estudio de su dimensión cultural y económica (Estudios) - Abad Merchán, Guido Andrés (2020)
This article presents chronologically historical-cultural and economic facts of cocoa in Ecuador. Through the metaphor of the fabric, a double look of its history is established, considering that it has been one of the most important primary export products of Ecuador. This research aims to describe the main elements of the cultural and economic dimension related to the history of cocoa on the Ecuadorian coast and helps in understanding the articulation of these dimensions. It is based on the descriptive method with the techniques of documentary and bibliographic analysis in historical perspective, to demonstrate the importance of the cultural sense of cocoa linked to the economic aspect of the product. The metaphor presented here indicates that the warp of the cocoa fabric is related to the less visible factors and refers to the historical and cultural aspects of the product; the plot, which is the most visible, corresponds to the economic and commercial context of cocoa. The article highlights some elements that make up the dimensions of analysis and that may serve to deepen the magnitude or direction of their interrelations.